PENGEMBANGAN SISTEM REKOMENDASI UNTUK SIMULASI RAKIT KOMPUTER MENGGUNAKAN ALGORITMA GENETIKA BERBASIS WEBSITE - Maulana, Vieri Arief; Haromainy, Muhammad Muharrom Al; Nurlaili, Afina Lina (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2025)
This research develops a web-based recommendation system for computer assembly simulations using genetic algorithms. The system is designed to assist users in selecting optimal computer components based on their available budget and desired performance. Component data were collected from e-commerce platforms and online sources, then preprocessed using Min-Max normalization to ensure balanced data scaling. The system was developed using Laravel for the frontend interface and Flask API for computational processing of the genetic algorithm. System evaluation was conducted using the System Usability Scale (SUS) method involving 21 respondents, resulting in an average score of 86.67, which falls into the